Internal audit and risk management practices in Malaysian higher education institutions - Wan Mustapha, Wan Musnida; Zainal Abidin , Nor Hafizah; Zakaria, Zamzulaila (2015)
Increasing trends of malpractices case among the HEI raised major concerns towards integrity and accountability of HEI in managing the public fund. There are growing interests among the public HEIs in establishing risk management and internal audit practices. This study addresses the extent of risk management practices in HEI and role of internal audit on risk management process. Findings show that all public HEIs do have an internal audit unit which is in line with the requirement of Treasury Circular No. 2/2004. Almost more than two third of the respondents involve in evaluating the effectiveness of risk management process. Two older HEIs already have established and advanced level of risk management process. While, majority of the newer HEIs are still in level of basis and developing stage of risk management process. The findings provide insights on current practices of public HEIs in the area of risk management and internal audit.